The roles of organizational justice, trustworthiness, trust and propensity of trust in the relationship of LMX with OCB and job satisfaction - Kuşculuoğlu, Sema (My University, 2008)
unknown
Keywords: Güven; İş Tatmini; Örgütsel Vatandaşlık Davranışı; Yönetici-Çalışan İlişkisi